APPLICATION OF VISUAL STUDIO .NET ON CATIA V5 IN ORDER TO OBTAIN AUTOMATION FOR FINITE ELEMENT ANALYSIS OF WING-BOX STRUCTURES - RAHMADIAN PAMUNGKAS (NIM 23605301), IQBAL
This thesis presents an application of object oriented approaches in Visual Studio .NET environment that they were selectively linked to component object modeling (COM) of CATIA V5. It has been developed three consecutive software applications for having specific purpose. The first application was developed to generate surface of wing (lifting Surface) by parameter of number of kink and orientation of airfoils. By referenced to the first, the second application is able to generate structural layout of wing-box based on parameter of number of stringers and ribs. The last application conducted as finite element model generator and definition of properties. Visual Basic and Visual C++ .Net have been implemented proportionally with respect to strength on accessibilities. CATIA V5-R17 P2 is been utilized to perform particular link to explore some specific object of CAD. As a result, those applications could perform high level of automation in generating surface until finite element analysis. Some case studies have been done to evaluate this concept and to demonstrate the performance of this application.